Gut dysbiosis in autoimmune diseases: Association with mortality - Chang, Sung-Ho; Choi, Youngnim (Frontiers in Cellular and Infection Microbiology, 2023)
To better understand the impact of gut dysbiosis on four autoimmune diseases [Sjögren’s syndrome (SS), systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and multiple sclerosis (MS)], this review investigated the altered gut bacteria in each disease and the shared ones among the four diseases. The enriched gut bacteria shared by three of the four autoimmune diseases were Streptococcus, Prevotella, and Eggerthella, which are associated with autoantibody production or activation of Th17 cells in immune-related diseases. On the other hand, Faecalibacterium comprises depleted gut bacteria shared by patients with SLE, MS, and SS, which is associated with various anti-inflammatory activities. The indexes of gut dysbiosis, defined as the number of altered gut bacterial taxa divided by the number of studies in SLE, MS, RA, and SS, were 1.7, 1.8, 0.7, and 1.3, respectively. Interestingly, these values presented a positive correlation trend with the standardized mortality rates —2.66, 2.89, 1.54, and 1.41, respectively. In addition, shared altered gut bacteria among the autoimmune diseases may correlate with the prevalence of polyautoimmunity in patients with SLE, SS, RA, and MS, that is, 41 percent, 32.6 percent, 14 percent, and 1–16.6 percent, respectively. Overall, this review suggests that gut dysbiosis in autoimmune diseases may be closely related to the failure of the gut immune system to maintain homeostasis.